Correction: Blood pressure control in chronic kidney disease: A cross-sectional analysis from the German Chronic Kidney Disease (GCKD) study - Schneider, Markus; Hilgers, Karl Friedrich; Schmid, Matthias; Hübner, Silvia; Nadal, Jennifer; Seitz, David; Busch, Martin; Haller, Hermann; Köttgen, Anna; Kronenberg, Florian; Baid-Agrawal, Seema; Schlieper, Georg; et al. (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0202604.].
EVALuna2:205518